The genome sequence of the Montseny horsehair worm, Gordionus montsenyensis sp. nov., a key resource to investigate Ecdysozoa evolution - Eleftheriadi, Klara; Guiglielmoni, Nadège; Salces-Ortiz, Judit; Vargas-Chavez, Carlos; Martínez-Redondo, Gemma I.; Gut, Marta; Flot, Jean-François; Schmidt-Rhaesa, Andreas; Fernández, Rosa (Peer Community Journal)

(untitled)
Nematomorpha, also known as Gordiacea or Gordian worms, are a phylum of parasitic organisms that belong to the Ecdysozoa, a clade of invertebrate animals characterized by molting. They are one of the less scientifically studied animal phyla, and many aspects of their biology and evolution are still unknown, partially due to the lack of genomic resources for this phylum. As part of the European Reference Genome Atlas pilot effort to generate reference genomes for European biodiversity, we present the taxonomic description and chromosome-level genome assembly of a newly described species of Nematomorpha (Gordionus montsenyensis Schmidt-Rhaesa & Fernández sp. nov.). The final assembly has a total length of 288 Mb in 396 scaffolds with an N50 of 64.4 Mb, 97% of which is scaffolded into 5 pseudochromosomes. The circular mitochondrial genome was also assembled into a 15-kilobases sequence. Gene annotation predicted 10,320 protein-coding genes in the nuclear genome. In this study, we contribute a key genomic resource to not only explore the evolution of Ecdysozoa, but also to further our understanding on the genomic basis of parasitic lifestyles. In addition, we describe a species new to science from this enigmatic animal phyla.